Capsular Sialyltransferase Specificity Mediates Different Phenotypes in Streptococcus suis and Group B Streptococcus - Roy, David; Takamatsu, Daisuke; Okura, Masatoshi; Goyette-Desjardins, Guillaume; Van Calsteren, Marie-Rose; Dumesnil, Audrey; Gottschalk, Marcelo; Segura, Mariela (Frontiers in Microbiology, 2018)
The capsular polysaccharide (CPS) represents a key virulence factor for most encapsulated streptococci. Streptococcus suis and Group B Streptococcus (GBS) are both well-encapsulated pathogens of clinical importance in veterinary and/or human medicine and responsible for invasive systemic diseases. S. suis and GBS are the only Gram-positive bacteria which express a sialylated CPS at their surface. An important difference between these two sialylated CPSs is the linkage between the side-chain terminal galactose and sialic acid, being alpha-2,6 for S. suis but alpha-2,3 for GBS. It is still unclear how sialic acid may affect CPS production and, consequently, the pathogenesis of the disease caused by these two bacterial pathogens. Here, we investigated the role of sialic acid and the putative effect of sialic acid linkage modification in CPS synthesis using inter-species allelic exchange mutagenesis. To this aim, a new molecular biogenetic approach to express CPS with modified sialic acid linkage was developed. We showed that sialic acid (and its alpha-2,6 linkage) is crucial for S. suis CPS synthesis, whereas for GBS, CPS synthesis may occur in presence of an alpha-2,6 sialyltransferase or in absence of sialic acid moiety. To evaluate the effect of the CPS composition/structure on sialyltransferase activity, two distinct capsular serotypes within each bacterial species were compared (S. suis serotypes 2 and 14 and GBS serotypes III and V). It was demonstrated that the observed differences in sialyltransferase activity and specificity between S. suis and GBS were serotype unrestricted. This is the first time that a study investigates the interspecies exchange of capsular sialyltransferase genes in Gram-positive bacteria. The obtained mutants represent novel tools that could be used to further investigate the immuno-modulatory properties of sialylated CPSs. Finally, in spite of common CPS structural characteristics and similarities in the cps loci, sialic acid exerts differential control of CPS expression by S. suis and GBS